2017
DOI: 10.1002/jclp.22494
|View full text |Cite
|
Sign up to set email alerts
|

Driving Aggression and Anxiety: Intersections, Assessment, and Interventions

Abstract: Objective: Driving aggression and anxiety are significant contributors to risky driving and motor vehicle crashes (MVCs), which are leading causes of U.S. morbidity and mortality. Even though aggression and anxiety can be conceptualized as related features of the fight-or-flight response, literature on these topics has not been integrated. Driving aggression and anxiety are also transdiagnostic constructs that span multiple psychiatric disorders. Assessment and treatment of these complex problems must be under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 147 publications
(285 reference statements)
0
10
1
Order By: Relevance
“…In fact, Rowden et al [10] noted that hazard detection encourages the driver to adopt a more responsible behavior in driving, thereby reducing offenses, and given the short term intervention applied, it is a positive outcome for the intervention group, which could mean that long-term intervention could be possible to make a significant difference. Our findings, even though not as strong as reported in Zinzow et al [17], who found a 29% decline in aggressive driving and a 21% decline in risky driving, suggest that such interventions, if appropriately redesigned, can prove to be useful in terms of reducing risky self-reported driving behavior and stress levels while driving.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In fact, Rowden et al [10] noted that hazard detection encourages the driver to adopt a more responsible behavior in driving, thereby reducing offenses, and given the short term intervention applied, it is a positive outcome for the intervention group, which could mean that long-term intervention could be possible to make a significant difference. Our findings, even though not as strong as reported in Zinzow et al [17], who found a 29% decline in aggressive driving and a 21% decline in risky driving, suggest that such interventions, if appropriately redesigned, can prove to be useful in terms of reducing risky self-reported driving behavior and stress levels while driving.…”
Section: Discussioncontrasting
confidence: 69%
“…It seems from the review that such interventions are still missing from road safety research despite the wealth of evidence in support of these interventions from other fields of research. Novel interventions using virtual reality and simulation-induced cognitive restructuring in anxiety and anger management have only recently emerged and been tested in pilot studies [17]. Emphasis is thus placed on the need to develop targeted interventions with cognitive restructuring approaches tailored to the special characteristics of various population groups [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason we genotyped the participants of a longitudinal study of traffic behaviour. Risky driving and traffic accidents are in strong relationship with aggressive and anxious states while driving, and share such affective and cognitive characteristics as emotional reactivity and threat appraisal (Zinzow and Jeffirs, 2018). We have previously shown in the EPSTB Sample 1 of this study that driving while impaired is highly recurrent, and that even in terms of other, additional traffic violations the repeat DWI drivers represent the most hazardous group of car drivers (Tokko et al, 2019).…”
Section: Discussionmentioning
confidence: 63%
“…So far, most of the intervention programs have focused on ignition interlocks, education programs, victim impact panels, Intensive Supervision Programs, and DUI courts -but there are very little data reporting their efficacy (Ferguson, 2012;Miller et al, 2015;Nochajski and Stasiewicz, 2006;Rider et al, 2006). By the other hand, although incipient, studies evaluating interventions targeting drivers with traffic risk taking behaviors and transgressions are showing interesting improvement after cognitive-behavioral treatments (Sommers et al, 2013;Strom et al, 2013;Zinzow and Jeffirs, 2018). For Miller et al (2015), multicomponent treatment -that arises from its ability to respond to the complexity and combination of legal, social and psychological factors that are associated with DUI behavior -may work best as preventive interventions.…”
Section: Discussionmentioning
confidence: 99%